Broad-spectrum mildew resistance in Arabidopsis thaliana mediated by RPW8 - Xiao, Shunyuan; Ellwood, Simon; Calis, Ozer; Patrick, Elaine; Li, Tianxian; Coleman, Mark; Turner, John (The American Association for the Advancement of Science, 2001)
Plant disease resistance (R) genes control the recognition of specific pathogens and activate subsequent defense responses. We show that the Arabidopsis thaliana locus RESISTANCE TO POWDERY MILDEW8 (RPW8) contains two naturally polymorphic, dominant R genes, RPW8.1and RPW8.2, which individually control resistance to a broad range of powdery mildew pathogens. Although the predicted RPW8.1 and RPW8.2 proteins are different from the previously characterized R proteins, they induce localized, salicylic acid–dependent defenses similar to those induced by R genes that control specific resistance. Apparently, broad-spectrum resistance mediated by RPW8 uses the same mechanisms as specific resistance.